Compound and heterozygous mutations of KCNQ1 in long QT syndrome with familial history of unexplained sudden death: Identified by analysis of whole exome sequencing and predisposing genes. Issue 1 (29th September 2019) - Lin, Yubi; Zhao, Ting; He, Siqi; Huang, Jiana; Liu, Qianru; Yang, Zhe; Qin, Jiading; Yu, Nan; Lu, Hongyun; Lin, Xiufang
Abstract: Introduction: Long QT syndrome (LQTS) increases the risk of life‐threatening arrhythmia in young individuals with structurally normal hearts. Sixteen genes such as the KCNQ1, KCNH2, and SCN5A have been reported for association with LQTS. Case presentation: We identified the compound heterozygous mutations in the KCNQ1 gene at c. G527A (p.W176X) and c.G1765A (p.G589S) predicted as "damaging." The in‐silico analysis showed that when compared to the characteristics of mRNA and protein of wild‐type KCNQ1, the mRNA of c.G527A mutation was significantly different in the centroid secondary structure. The subunit coded by W176X would lose the transmembrane domains S3–S6 and helices A‐D. The protein secondary structure of G589S was slightly shortened in helix structure; the protein physics‐chemical parameters of W176X and G589S significantly and slightly changed, respectively. Conclusions: The compound heterozygous mutations of W176X and G589S coexisting in KCNQ1 gene of homologous chromosomes, resulting in more severe phenotype, are the likely pathogenic and genetic risks of LQTS and USD in this Chinese family.